Penyimpangan Prinsip Kesantunan Berbahasa di Kalangan Remaja Suku Dayak Kanayan Dialek Ahe Kabupaten Bengkayang Kalimantan Barat - Husni Dwi Syafutri; Siti Arnisyah; Rian Novita; Ester Ester; Ernawati Ernawati (Universitas Batanghari Jambi, 2023)
This study aims to describe the deviation of politeness among adolescents in Kanayan Dayak Ahe. The method used in this research is a qualitative method to reveal the types of deviations. The focus of this research is Language Politeness among Adolescents of the Dayak Kanayan Tribe of Ahe Dialect using sociopragmatic studies. The results of this study indicate that there are types of deviation from the principle of language politeness used in the interaction of the youth of the Kanayan ethnic group. Ahe dialect consists of: (1) wisdom maxim, (1) maxim of generosity, (3) maxim of charity, (4) maxim of humility, (5) maxim of compatibility, and (6) maxim of sympathy. The politeness scale of a speech is held as a measure or indicator of the politeness of a speech act in both formal and informal situations